The research journal TRANSPORT: peer-reviewing process in 2014 - Prentkovskis, Olegas; Junevičius, Raimundas (Transport, 2014)
The research journal TRANSPORT: peer-reviewing process in 2014. First Published Online: 16 Dec 2014